Identifikasi Jenis dan Kategorisasi Kata Pembentuk Reduplikasi dalam Media Cetak Lokal - Noviatri, Noviatri (Universitas Andalas, 2024)
The background to writing this article was the variety of linguistic phenomena in reduplication used in local print media. This phenomenon is evident in the diversity of types and categories of essential words/primary forms that form reduplication. This research aims to describe the types and categorization of words that form reduplication in local print media. There are three research methods and techniques used in this paper, namely: methods and techniques for providing data; methods and techniques for data analysis; and methods and techniques for presenting data analysis results. In providing data, the observation method is used with basic techniques, tapping techniques, advanced techniques, skillful free-involvement listening techniques, and note-taking techniques. The matching process and the addition method were used to analyze the data. An informal presentation method is used to present the results of data analysis. The population of this study consisted of reduplications used in two local print media, namely the Padang Ekspress and Singgalang newspapers. The research sample was reduplication in the Padang Ekspress and Singgalang newspapers published from January to August 2024. The findings in this research are based on the type of reduplication, there are four types of reduplication used in local print media, namely complete/whole reduplication, partial reduplication, reduplication with a combination of affixes/affixes, and phoneme-changing reduplication. Based on the categories of words that form reduplication, reduplication in local print media is formed by repeating ten categories of essential words/primary forms, namely repetition of basic words/basic forms in the categories of noun (KB), verb (KK), adjective (KS), word numbers (Kbil.), question words (KT), pronouns (KG), demonstrative words (KP), adverbs (adv.), unique morphemes (MU), and words of greeting (KSp).